Glass Foam Made with Silicon Nitride and Manganese Oxide by Microwave Irradiation - Marius Florin Dragoescu; Lucian Paunescu; Sorin Mircea Axinte (Newinera Publisher, 2021)
A high mechanical strength (6.1 MPa) glass foam was produced by sintering/foaming at 830 ºC in an experimental 0.8 kW-microwave oven. The basic raw material was a colorless flat glass waste and the foaming agent was Si3N4 powder (2 wt.%). As an oxygen supplying agent, a MnO2 powder (3.1 wt.%) was used. The main physical, mechanical, thermal and morphological characteristics of the optimal sample were: apparent density of 0.47 g/cm3, porosity of 77.6%, thermal conductivity of 0.105 W/m·K, compressive strength of 6.1 MPa and pore size between 0.15-0.40 mm. The optimal glass foam sample has the required characteristics of a thermal insulation material usable under mechanical stress conditions in civil engineering. The originality of the paper is the application of the unconventional microwave heating technique, faster and more economical, unlike the other papers in the same area published in the literature, followers of the traditional conventional heating technique.